Understanding Anemia - Uthman, Ed (Book collections on Project MUSE., 1998)
"Understanding Anemia gently builds upon elementary knowledge of biology to provide the general reader with a fairly sophisticated understanding of the various causes of anemia, the methods used to make diagnoses, and the principles of treatment. The book begins with a definition of anemia and a brief history of the scientific study of blood. It explains how the doctor makes the diagnosis and details the main types of anemia. Since the different conditions result from the failure of various organs, the reader will come away with a surprisingly broad understanding of human anatomy and physiology, encompassing the digestive, circulatory, and immune systems, nutrition, biochemistry, and heredity."--Jacket